THE VILLAGES AS SOCIAL AND ECONOMIC COMMUNITIES (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2003)
The ethnic region of Gorna Reka is situated in the North-west part of the Republic of Macedonia, covering the upper part of the river Radika, up to Boshkov bridge on the South. According to the basic characteristics of the terrain, the whole ethnographic space is a mountainous region. Figuratively speaking, the region of Gorna Reka, according its natural setting, seems as an "ethnic tromp", it is isolated from the neighbouring regions with natural obstacles: mountains and rivers. The population, that has been structured through specific ethno-historical processes, today consists of Christian Macedonians and Muslim Albanians. The basic economic activities are cattle breeding and economic emigration, activities that influenced the development of the ethnic culture as a whole. Living in such a naturally isolated geographic settlement, without having a bigger urban centre near by, the population of Gorna Reka did not have a big possibility to communicate with the neighbouring regions. This is why they developed their own material, social and spiritual elements of culture. The way the village is organised as a community, that covers the rules of behaviour of its members, through nominating village employees of different kind, is a part of social life. Most of those characteristics are common for all South Slavs, but as well as for other Balkan populations.
Keywords: Gorna REka; village council; village board; kmet; peace council; church council; collective ownership; self-assistance